Pengaruh Likuiditas, Leverage, Profitabilitas, Firm Size dan Growth Opportunity terhadap Hedging Sektor Farmasi, Industri Dasar dan Bahan Kimia pada Perusahaan ISSI - Ratih Ratnaningsih; Destian Arshad Darulmalshah Tamara; Ine Mayasari (Journal of Applied Islamic Economics and Finance, 2021)
Pharmaceutical sector companies as well as basic industries and chemicals in Indonesia still depend on imports of medicinal raw materials using foreign currency. Forex fluctuations are unavoidable and one of the risk management for foreign exchange fluctuations is hedging. This study aims to determine and analyze the involvement of Current Ratio representing Liquidity, Debt to Equity Ratio representing Leverage, Ratio On Assets representing Profitability, Firm Size and Growth Opportunity to hedging case studies in Pharmaceutical Sector Companies and Basic and Industrial Industries. Chemicals indexed by the Indonesian Sharia Stock Index on 2015 – 2020. Purposive sampling method used for sample selection and logistic regression analysis. Result on this research, the concluded that in the Pharmaceutical Industry and Basic Industry and Chemicals listed in ISSI for the 2015-2020 period, the variables that affect the hedging decision making are Firm Size and Growth Opportunity